Model ITPOSMO untuk Evaluasi Keberhasilan Aplikasi Bravo - Ramanda, Kresna; Awaludin, Rizky; Puspitasari, Diah; Sikumbang, Erma Delima (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
Bravo-PUPR application problems are caused by many factors, inaccurate data, inadequate integration, technical infrastructure and high process complexity. In addition, inconsistencies between organizational values and digital innovation, lack of training, weak coordination, and external support are also obstacles to the success of such e-government. To find the success rate of the Bravo-PUPR application, we used the ITPOSMO model to assess the gaps between the designs realized in the application. Of the 39,308 employees in the population used for the study, only 100 met the criteria to be selected using the Purpose Sampling technique. Quantitative data analysis is used, primarily to test for gaps. As a result, the Other Resource dimension received the lowest GAP score, which was 0.09. In addition, Staffing and Skills dimension received a score of 0.76, Objective and value obtained a score of 1.17, Technology obtained a score of 1.61, Information obtained a score of 1.69, and Management and Structure obtained a score of 1.82. The highest GAP score in the Process dimension is 2.44. This score is obtained based on the calculation of the overall assessment table. The project may have been successful due to its overall rating of 9.58, which ranges from 0 to 14.